Characterization of solid dosage forms covered by spray coating process - Murillo-Fernández, Mac Arturo (2019)
This research seeks to contribute to the development of a pioneering methodology for the characterization of pharmaceutical tablets during the coating process, by means of random spraying, using several techniques. The aim is to support the development of a viable option for systems of greater complexity, high volume production and information processing. Partial results show patterns of behavior that can be used to facilitate the development of devices and automatable methodologies, applicable to similar processes that can impact the coating processes as key factors of quality and productive management.